Relationship Between Fatigue and Changes in Swim Technique During an Exhaustive Swim Exercise - Bassan, Natalia M. [UNESP]; Cesar, Tadeu E. A. S. [UNESP]; Denadai, Benedito S. [UNESP]; Greco, Camila C. [UNESP] (Human Kinetics Publ Inc, 2016)
Purpose: To analyze the relationship between the responses of isometric peak torque (IPT) and maximal rate of force development (RFDmax) with the changes in stroking parameters in an exhaustive exercise performed in front crawl. Methods: Fifteen male swimmers performed, on different days, the following protocols: maximal 400-m trial, strength tests before and after an exhaustive test at 100% of the mean speed obtained during the 400-m test, and the same procedures on day 2. Results: The IPT of elbow flexors (79.9 +/- 19.4 and 66.7 +/- 20.0 N.m) and elbow extensors (95.1 +/- 28.0 N.m and 85.8 +/- 30.5 N.m) was decreased after the swim test, as was RFDmax (521.8 +/- 198.6 and 426.0 +/- 229.9 N.m/s; 420.6 +/- 168.2 and 384.0 +/- 143.5 N.m/s, respectively). Stroke length decreased during the swim test (1.96 +/- 0.22 and 1.68 +/- 0.29 m/stroke), while stroke rate increased (37.2 +/- 3.14 and 41.3 +/- 4.32 strokes/min). The propulsive phases increased while the nonpropulsive phases decreased during the test. Significant correlation was found between the changes in IPT and stroke length, stroke rate and recovery (elbow flexors), and entry and catch phase (elbow extensors). In addition, significant correlation was found between the changes in RFDmax of elbow flexors with the changes in pull and recovery phases. Conclusion: Changes in swim technique during an exhaustive test can be, at least in part, associated with fatigue of the arm muscles.
Keywords: neuromuscular; swimming; front crawl; evaluation and training